2016
DOI: 10.3389/fcimb.2016.00137
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of H9N2 Virus Invasion into Dendritic Cells by the S-Layer Protein from L. acidophilus ATCC 4356

Abstract: Probiotics are essential for the prevention of virus invasion and the maintenance of the immune balance. However, the mechanism of competition between probiotics and virus are unknown. The objectives of this study were to isolate the surface layer (S-layer) protein from L. acidophilus ATCC 4356 as a new antiviral material, to evaluate the stimulatory effects of the S-layer protein on mouse dendritic cells (DCs) and to verify its ability to inhibit the invasion of H9N2 avian influenza virus (AIV) in DCs. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 34 publications
(34 reference statements)
2
22
1
Order By: Relevance
“…The S-layer protein was immobilized on the ELISA plate, incubated with the respective DC-SIGN-hFc fusion proteins, and their interaction was quantitated by colorimetric detection (Figure 3A). As expected, a direct interaction was observed by this binding assay (Konstantinov et al, 2008; Lightfoot et al, 2015; Gao et al, 2016). We determined the calcium dependence of the DC-SIGN/S-layer interaction, incubating the proteins in the presence of EGTA.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The S-layer protein was immobilized on the ELISA plate, incubated with the respective DC-SIGN-hFc fusion proteins, and their interaction was quantitated by colorimetric detection (Figure 3A). As expected, a direct interaction was observed by this binding assay (Konstantinov et al, 2008; Lightfoot et al, 2015; Gao et al, 2016). We determined the calcium dependence of the DC-SIGN/S-layer interaction, incubating the proteins in the presence of EGTA.…”
Section: Resultssupporting
confidence: 89%
“…They are considered to function as protective coats, in the maintenance of cell shape, in ion exchange in the cell wall, and in adhesion to biotic and abiotic surfaces. We and others have shown that the interaction between the S-layer of Lactobacillus acidophilus , one of the major bacterial species found in human intestines, and DC-SIGN can act as a potent inhibitor of JUNV and H9N2 viral infections (Martínez et al, 2012; Gao et al, 2016; Prado Acosta et al, 2016). Given that L. acidophilus and S-layer are both categorized as “generally recognized as safe” (GRAS) (Dunne et al, 2001; Mohamadzadeh et al, 2008), there is interest in further characterizing this novel mechanism of inhibition in order to develop new therapeutics that would target alphaviruses and flaviviruses.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, mouse adapted influenza A virus (PR8) titer was reduced in RAW264.1 cells by L. gasseri SBT2055 [ 60 ]. In mouse bone marrow DCs, the inhibition of viral replication by L. acidophilus ATCC4356 S-layer protein was demonstrated [ 62 , 63 ]. Priming of cells with S-layer protein prior to H9N2 avian influenza virus infection inhibited the invasion and replication of the virus, stimulated the type I IFN signaling pathway, increased IL-10 mRNA, and decreased TNF-α mRNA expression [ 62 ].…”
Section: Probiotics and Immune Modulation In Viral Respiratory Infmentioning
confidence: 99%
“…DC-SIGN is a CLR present in DCs and macrophages, it is involved in the recognition of several viruses and other microbes, a key step in the entry of pathogens into the cell. Indeed, L. acidophilus ATCC4356 Slps stimulate the activation of mouse DCs by activating IFN-I signaling pathway, which inhibit invasion of DCs by influenza virus H9N2 ( Gao et al, 2016 ). In addition, L. acidophilus ATCC4356 Slps inhibit the Junin virus (JUNV) infection by interacting with DC-SIGN ( Martínez et al, 2012 ).…”
Section: Probiotic–host Interaction Via Extractable Surface Proteinsmentioning
confidence: 99%